A review on wear and corrosion behavior of thermal oxidation on titanium-based alloy for biomedical application - Arman Shah Abdullah (Tanjong Malim)
A review on wear and corrosion behavior of thermal oxidation on titanium-based alloy for biomedical application by Arman Shah Abdullah